How to Win Multispecies Friends and Influence Anthropocentric People: Review of Jane Mummery and Debbie Rodan, Imagining New Human–Animal Futures in Australia - Rutledge-Prior, Serrin (Humanimalia, 2023)
Jane Mummery and Debbie Rodan, Imagining New Human–Animal Futures in Australia. Australian Studies: Interdisciplinary Perspectives 5. Oxford: Peter Lang, 2022. xiv, 348pp., 14 fig. col., US$82.95 (hb).